Book review: Daly, A., (2018). Children, Autonomy and the Courts: Beyond the Right to be Heard - Robert Porter (Scottish Journal of Residential Child Care)
'Children, Autonomy and the Courts' is based upon Aoife Daly's PhD thesis, and presents her argument that Article 12 of the United Nations Convention on the Rights of the Child – which she refers to as the 'right to be heard' – does not go far enough in securing the rights of children in relation to court proceedings. In particular, Daly focuses on those proceedings where 'best interests of the child' is the paramount concern, and although there is a focus on private law, it is also of interest to those involved in child protection and welfare decision-making in public law. That this is an adaptation from a thesis is clear in the style and structure of the book. This is no reference book, nor a book that can be easily dipped into to extract particular information, but it takes the reader on a compelling journey, from illustrating the limitations of Article 12, through to the need for, and arguments in favour of, an autonomy principle, and its implementation.